2000
DOI: 10.1016/s0002-9270(00)00807-8
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of intestinal microflora is associated with reduction in abdominal bloating and pain in patients with irritable bowel syndrome

Abstract: The results of the study indicate that the administration of Lb. plantarum with known probiotic properties decreased pain and flatulence in patients with IBS. The fiber content of the test solution was minimal and it is unlikely that the fiber content could have had any effect. This type of probiotic therapy warrants further studies in IBS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
250
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(260 citation statements)
references
References 19 publications
4
250
2
4
Order By: Relevance
“…In 95% of patients, after 4 weeks of oral administration of a probiotic L. plantarum 299v, a definite improvement of physiological parameters was observed, especially in terms of a reduced incidence of bloating connected with breaking wind. This effect was also maintained for as long as 12 months after the completion of probiotic administration (Nobaek et al 2000;Niedzielin et al 2001). …”
Section: Irritable Bowel Syndromementioning
confidence: 92%
See 1 more Smart Citation
“…In 95% of patients, after 4 weeks of oral administration of a probiotic L. plantarum 299v, a definite improvement of physiological parameters was observed, especially in terms of a reduced incidence of bloating connected with breaking wind. This effect was also maintained for as long as 12 months after the completion of probiotic administration (Nobaek et al 2000;Niedzielin et al 2001). …”
Section: Irritable Bowel Syndromementioning
confidence: 92%
“…IBS is caused by changes in intestinal motor activity and disorders in the functioning of neurotransmitters, especially an excessive reaction to stimuli, caused by an abnormal functioning of the intestines as well as infections (Horwitz & Fisher 2001). The above-mentioned factors are directly connected with changes in the intestinal microflora (especially excessive proliferation of certain groups of bacteria in the small intestine) and the course of 'abnormal' fermentation, resulting in the production of considerable amounts of gases (King et al 1998;Nobaek et al 2000). Symptoms of IBS are also enhanced by one's tendency to swallow air (Haderstorfer et al 1989).…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…A 2014 meta-analysis [34] reported the pooled results from 3 RCTs involving 314 adult patients with IBS [35,36,37]. Compared with placebo, the use of L. plantarum 299v (DSM 9843) reduced IBS symptoms (RR 0.67, 95% CI 0.51-0.87), but it had no effect on global symptom or abdominal pain scores (standardized mean difference -0.18, 95% CI -0.60 to 0.25).…”
Section: Bacterial Probioticsmentioning
confidence: 99%
“…It has been shown that certain diseases and stress are associated with reduction of the intestinal Lactobacillus population (25,26) and supplementation with these bacteria improves the overall condition, showed both in experimental and clinical studies (27,28). Oral administration of L. plantarum DSM 9843, with known probiotic properties (29), and rose hip in combination is accompanied by a significant decrease in the number of Enterobacteriaceae. This must be regarded as beneficial because the family Enterobacteriaceae, in general, is pro-inflammatory and also includes many potentially pathogens.…”
Section: Caecum Histologymentioning
confidence: 99%